Analysis of the impact of the district public policy on disability for Bogotá on the levels of inclusion in the ICT sector (2023)
The social inclusion of people with disabilities in Colombia has been addressed by the country ́s public policies. However, this population faces difficulties in accessing different social sectors, which is aggravated by stigma and discrimination in society. To address this problema, public policies are required to reduce the exclusión gap and ensure equal opportunities and accesible spaces for all citiziens. In this context, Information and Communication Technologies (ICT) have been indentified as a key tool, since they provide effective tools for the development of capabilities and the realization of social and labor activities for people with disabilities, i.e., they contribute to the creation of a more inclusive and innovative society. In this sense, this paper analyzes the District Public Policy on Disability for Bogota and its impact on the inclusion of persons with disabilities through the use of ICTs durin the period 2016-2020. Thus, the dimensions and elements embodied in the Public Policiy on Disability for the District in which the ICT sector has an impact are examined. Additionally, the visions, axes and pillars of the District Development Plan “Bogotá mejor para todos” were analyzed how this policy has contributed to the improvement of the quality of life and welfare of this population, the way in which opportunities for access and participation in the digital environment are generated. During the perior under study, the implementation of the public policy on disability in Bogota has achieved significant progress thanks to ICT tolos, training and appropiation of these, however, some deficiencies were identified in terms of the baseline and monitoring of the PPDD.